β-FeOOH Interlayer With Abundant Oxygen Vacancy Toward Boosting Catalytic Effect for Lithium Sulfur Batteries - Yingying Li; Xifei Li; Xifei Li; Xifei Li; Youchen Hao; Alibek Kakimov; Dejun Li; Qian Sun; Liang Kou; Zhanyuan Tian; Le Shao; Cheng Zhang; et al. (Frontiers in Chemistry, 2020)
Due to the shuttle effect and low conductivity of sulfur (S), it has been challenging to realize the application of lithium-sulfur (Li-S) batteries with high performance and long cyclability. In this study, a high catalytic active CNTs@FeOOH composite is introduced as a functional interlayer for Li-S batteries. Interestingly, the existence of oxygen vacancy in FeOOH functions electrocatalyst and promotes the catalytic conversion of intercepted lithium polysulfides (LiPS). As a result, the optimized CNTs@FeOOH interlayer contributed to a high reversible capacity of 556 mAh g−1 at 3,200 mA g−1 over 350 cycles. This study demonstrates that enhanced catalytic effect can accelerate conversion efficiency of polysulfides, which is beneficial of boosting high performance Li-S batteries.